Deciphering neutrophil dynamics in the focal lesion tumor microenvironment to overcome immunosuppression in multiple myeloma - Rivera, Joshua; Yan, Qi; Daneshmandi, Saeed; Lannes, Romain; Katsuta, Eriko; Choi, JeeEun; Singh, Prashant; Belal, Ahmed; Alberico, Ronald; Lund, Ian; Schaefer, Megan; Hassan, Hamza; et al. (Blood, 2025)
Understanding the roles of myeloid cells in the tumor microenvironment (TME) has emerged as a promising strategy to identify novel targets to counteract the immunosuppressive barriers protecting multiple myeloma (MM). Neutrophils are a new cancer research focus due to their potential to reduce the efficacy of immune-based therapies. This study aimed to deepen understanding of neutrophil function in MM by analyzing freshly isolated myeloid cells from paired focal lesions (FLs) and bone marrow using single-cell RNA sequencing, immunofluorescence imaging, and functional assays. We describe 3 distinct CXCR2+ mature neutrophil subsets: TREM1+CD10+, RETN+LCN2+, and TNFAIP3+CXCL8+, each exhibiting unique phenotypes within the TME. Notably, the TREM1+CD10+ subset was highly prevalent, particularly in FLs, demonstrating potent immunosuppressive effects on T cells. This subset's gene signature was correlated with shorter overall survival (OS) in a large data set of patients with MM, underscoring its clinical significance. Targeted inhibition of neutrophil activity through CXCR2 blockade, alone or combined with standard anti-MM therapies, significantly reduced tumor burden, improving OS in preclinical MM models. These insights into neutrophil-mediated immunosuppression in MM provide valuable knowledge regarding mechanisms driving immune evasion, and reveal new therapeutic approaches to enhance the efficacy of MM treatment.